2005
DOI: 10.1038/sj.sc.3101726
|View full text |Cite
|
Sign up to set email alerts
|

A 25-year longitudinal study of the natural course of aging after spinal cord injury

Abstract: Study design: Longitudinal; Survey. Objective: The purpose of this study was to investigate the natural course of changes in activity patterns, health indicators, life satisfaction, and adjustment over 25-year period among people with spinal cord injury (SCI) in the USA. Setting: The preliminary data were collected from a Midwestern United States university hospital of the USA, whereas the follow-up data were collected at a large Southeastern United States rehabilitation hospital. Method: The Life Situation Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Those individuals in their 20s at baseline showed improved satisfaction with employment after 25 years, in addition to lowered satisfaction with social and sex lives, and general health as assessed by the LSQ. 35 Satisfaction with living arrangements and finances remained unchanged. 35 In a 20-year study with three follow-up time points, Krause 36 similarly found satisfaction with employment to improve, whereas satisfaction in the other five areas assessed by the LSQ (that is, living arrangements, finances, social life, sex life, general health) remained unchanged.…”
Section: Swlsmentioning
confidence: 89%
See 2 more Smart Citations
“…Those individuals in their 20s at baseline showed improved satisfaction with employment after 25 years, in addition to lowered satisfaction with social and sex lives, and general health as assessed by the LSQ. 35 Satisfaction with living arrangements and finances remained unchanged. 35 In a 20-year study with three follow-up time points, Krause 36 similarly found satisfaction with employment to improve, whereas satisfaction in the other five areas assessed by the LSQ (that is, living arrangements, finances, social life, sex life, general health) remained unchanged.…”
Section: Swlsmentioning
confidence: 89%
“…Successful aging is said to occur when individuals compensate for physical or functional losses by engaging in and focusing on fewer yet more desired activities in attempts to enrich life. Although the SCI literature reports that QoL remains high and stable over time, findings have also shown variation in several QoL domains, such as increasing satisfaction with employment [35][36][37][38] and diminishing satisfaction with social and sex lives. 35,39 It is therefore plausible that increasing satisfaction with employment may compensate for decreasing satisfaction with social and sex lives, as per the Life Span Development theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 There were several similarities with the earlier research over shorter intervals. [7][8][9] In addition to the aforementioned survivor effect, there was a combination of favorable and unfavorable changes. Participants were clearly less active socially and continue to report a greater number of health problems, with corresponding diminished satisfaction in related areas.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several reports on a longitudinal cohort have been reported over a 30-year interval. [5][6][7][8][9] Changes in outcomes have evolved over time. There has been a mixed pattern of favorable and unfavorable changes, with general improvements in employment outcomes, overall adjustment, and satisfaction with employment and finances.…”
Section: Introductionmentioning
confidence: 99%